Contextualizing Internationalization at Home: academic perspectives from Cypriot higher education in a changing global landscape - Soule, Maria Victoria (Frontiers in Education, 2025)
This article explores academic staff perceptions and practices of Internationalization at Home (IaH) in the context of higher education in the Republic of Cyprus. Although IaH is increasingly promoted as a strategy for embedding international and intercultural dimensions into the formal and informal curriculum, its implementation varies depending on institutional and academic contexts. This study focuses on three key variables–academic rank, discipline, and institution type–to better understand how institutional and academic contexts shape faculty engagement with IaH. Drawing on data from 76 academic teaching staff across six universities, the study employs both quantitative (three-way ANOVA) and qualitative (Qualitative Content Analysis) approaches, based on insights gathered through a survey. The findings reveal that while most participants integrate some form of IaH into their teaching, notable differences emerge across ranks and disciplines. Senior academics are more likely to implement structurally supported activities, whereas junior staff rely on more accessible, student-centered strategies. STEM faculty tend to equate IaH with English-medium instruction and materials, while non-STEM staff report broader intercultural and pedagogical practices. These findings highlight the need for more context-sensitive approaches to IaH that consider differences in institutional positioning, pedagogical autonomy, and faculty development needs.